Perubahan Penggunaan Lahan Di Kawasan Wisata Air Terjun Sri Gethuk, Kabupaten, Gunungkidul, DIY - Hafidz Irshaddin (Gadjah Mada Journal of Tourism Studies, 2020)
Since its inception in 2010, the Sri Gethuk Waterfall Tourism Area has seen a steady increase in the number of tourists who visit. Prior to 2015, the highest number of tourism visits recorded was 140.315. This increasing sum has compelled the tourism site’s management to build supporting facilities in this tourism site. As these tourism-supporting facilities have been built on an annual basis, they have gradually transformed a land that was previously a forest and rainfed rice land. The purpose of this study is to learn more about the transformation of land use on the Sri Gethuk tourism site. It makes use of chronological or time series imagery data to learn about land use in 1999, 2007, 2011, 2013, 2015, 2017, and 2018. Additionally, the digitized data is analyzed with overlay techniques. The overlay analysis has obtained a new area as a result of the intersection from two changing of land use areas. This research discovers that there was a drastic change on two interval years, which were on 2011 until 2013 as the large change of the land reached 0,631664 Ha. Furthermore, the large change of the land on 2013 until 2015 reached 0,517924 Ha. Along the escalation of tourism visits, the supporting tourism facilities had been built on this tourism site on 2011 until 2015, for instance: parking lots, prayer room, stalls, toilet, pathway, hall, gazebo, and concreting the dock area.